The Phenomena La Hoguette and Limburg – Technological Aspects - Kirschneck Erich (De Gruyter, 2021)
La Hoguette and Limburg pottery and the role their producers played in the Neolithization of western Central Europe are still a matter of debate. These styles exist in parallel to Linearbandkeramik (LBK) but are different from LBK pottery and here called Non-LBK wares. The various Non-LBK styles are mainly defined based on decoration, but this does not coincide with important technological features. Therefore, an technological approach including the parameters of temper, vessel morphology, and firing methods was used for an alternative classification and to trace knowledge transmission networks. It is suggested that several technologically distinguishable Non-LBK pottery traditions of different geographical origins existed contemporaneously in western Central Europe. While the early mineral- and organic-tempered ware shows some similarities with the Earliest and Early LBK, the widespread early bone-tempered pottery with its uniform design cannot be traced back to either Cardial or LBK pottery. This is probably the oldest pottery in western Central Europe. This means that here pottery emerged first as a tradition outside both the LBK and Cardial cultures. Increasing interaction between producers of various Non-LBK wares and LBK pottery makers can then be traced over several centuries. All styles are shown to be diverse and dynamic and to be undergoing substantial internal development. The persistent mutual influencing is a key for understanding the development of Non-LBK pottery, as well as for innovations within LBK ceramic production. Here, a hypothesis is proposed that the makers of Non-LBK wares may be hunter-gatherers, although this cannot currently be proven.